2014
DOI: 10.5539/jfr.v3n4p93
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile and CLA Content of Goat Milk: Influence of Feeding System

Abstract: There is great interest in producing bioethanol from biomass and there is much emphasis on exploiting The effect of pasture and of diet linseed supplementation on fatty acid profile of milk was evaluated using 45 pluriparous goats, equally divided after kidding into three homogeneous groups (H, P and L). Group H (control) and L were housed in a stall receiving alfalfa hay, while group P was led to pasture. The groups received concentrate which for group L had linseed as ingredient. Average milk yield did not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
3
8
0
1
Order By: Relevance
“…The lipids from goat's milk contain several hundred fatty acids of whose percentage from the total of fatty acids varies considerably [9]. Medium-chain triglycerides normally reach a percentage of 36% in milk goat in comparison with 21% in cow milk, thereby reducing the synthesis of endogenous cholesterol [10].…”
Section: Tabel 3 Concentration Of Types Of Total Fatty Acid In Goat Mmentioning
confidence: 99%
“…The lipids from goat's milk contain several hundred fatty acids of whose percentage from the total of fatty acids varies considerably [9]. Medium-chain triglycerides normally reach a percentage of 36% in milk goat in comparison with 21% in cow milk, thereby reducing the synthesis of endogenous cholesterol [10].…”
Section: Tabel 3 Concentration Of Types Of Total Fatty Acid In Goat Mmentioning
confidence: 99%
“…Tudisco et al (2014) who evaluated the effect of pasture on the fatty acid profile of goat milk reported that goats on pasture showed higher amounts of CLA in their milk in comparison with the control animals. It is well documented that although dietary supplementation of CLA for dairy ruminants can increase the amounts of CLA in their milk, CLA has a reducing effect on milk fat of dairy ruminants, especially cows and sheep which has been mostly attributed to a decrease in biosynthesis of lipids.…”
Section: Concentration Of Cla In Ruminant Milk Fatmentioning
confidence: 99%
“…This situation is consistent with the report made by Güler et al (2007) that informed significant changes in the fatty acids except of short-chain fatty acids during lactation for the German Fawn x Hair goat crossbreds and Shami goats. Similarly, Tudisco et al (2014) reported that fatty acids of goats' milk were changed as a function of sampling month. Fatty acids up to partly C16 are de novo synthesized within the mammary gland from acetate and butanoate produced by rumen bacteria.…”
Section: Data Analysesmentioning
confidence: 97%
“…In contrast to the previous study for Shami breed (Güler et al, 2007) octadecanoic acid in milk of all groups during the trial was significantly higher than its unsaturated isomers such as 9-octadecenoic and 9,12-octadecadienoic acids. Tudisco et al (2014) and Sanz-Sampelayo et al, (2007) reported that predominant FFA with 18 carbons was octadodecanoic acid in goat milk and its unsaturated isomers could be dependent mostly on the pasture and also the activity of desaturase enzyme in mammary cells of ruminants since this enzyme could be converted saturated C18 to unsaturated C18 isomers. However, cyclopropene acids found in some plants are inhibited to enzyme activity (Wastra, et.al., 2006).…”
mentioning
confidence: 99%